Mikroenkapsulasi Antosianin Kulit Buah Kakao (Theobroma cacao L.) Dengan Metode Koaservasi Kompleks: Microencapsulation of Anthocyanine of Kakao (Theobroma cacao L.) Bark with Complex Coaservation - Lubis, Siska Syahfitri; Sulastri, Evi; Zubair, Muhammad Sulaiman (Universitas Tadulako, 2018)
Anthocyanin is a class of antioxidants that are widely found in the skin of cocoa fruit (Theobroma cacao L.). Anthocyanin degradation occurs not only during the extraction process from plant tissues but also during the storage process. The microencapsulation process can protect the active substance from environmental influences or improve the stability of the preparation. This study aims to characterize anthocyanin microcapsules from cocoa (Theobroma cacao L.) fruit peel using a complex coacervation method, therefore, it can provide economic value added from this plant. Anthocyanin microencapsulation was formulated using a coating of gelatin: arabic gom with different concentrations of 1:1, 3:2, and 2:1. Microcapsule characterization was organoleptic and morphological test, particle size distribution, moisture content test, absorption efficiency, recovery test, antioxidant activity of the preparation, and FTIR analysis. The results showed that extract yield was 39.82%, optimum microcapsule characterization was obtained from 1: 1 concentration with 36.65% recovery test, 80.40% absorption efficiency, and antioxidant activity with IC50 of 20.52 ppm.